Proximate Composition, Levels of Some Essential Mineral Elements and Anti-Nutritional Components of Some Yam Species Found in Minna, Niger State - Godfrey, Eneogwe Okechukwu; Esther, Ibrahim Izihyi; Faith, Obuye (Biology, Medicine, & Natural Product Chemistry, 2023)
Samples of Dioscorea dumenturom, Dioscorea rotundata and Dioscorea cayenensis were investigated for their proximate composition, anti-nutritional and mineral contents using standard analytical methods. These varieties of Dioscorea analysed showed a significant difference (P≤0.05) amongst them. However, from the results, it was observed that Dioscorea rotundata had the highest ash (8.05±0.05 %) and crude fibre content (13.11±0.10 %) which indicates that it contains more mineral stuffing and is best for softening of stool. Dioscorea cayenensis had the highest fat content (16.31±0.30 %), indicating that it is a better source of calories than other yam species analysed. Dioscorea dumenturom had the lowest moisture content (3.51±0.01 %) as well as the highest crude protein (12.29±0.01 %) and carbohydrates (69.04±0.10 %) than other yam species analysed, indicating its longer shelf-life, high bodybuilding capacity and better source of energy than other yam species analysed. The anti-nutritional constituent of alkaloid and tannin were lowest in Dioscorea cayenensis while Dioscorea rotundata had the least cyanide, phytate and oxalate content. This implies that these particular yams are safer for consumption. The elemental analysis in mg/100g indicated that the yam species contained appreciable levels of essential minerals, with Dioscorea dumenturom having the highest sodium, calcium, iron, potassium, phosphorous and magnesium concentration of 32.05±0.07 mg/100g,190.57±0.01mg/100g, 5.98±0.03 mg/100g, 80.12±0.17 mg/100g, 237.10±0.48 mg/100g and 100.22±0.03 mg/100g respectively. All these mineral concentrations exist within the permissible limit of WHO and hence indicate that the yam species can serve as a good source of minerals.